Levels of Platelet Factor 3 in Citrate Plasma and in Whole Blood as Determined by A Chromogenic Peptide Substrate Assay - Sandberg, H.; Gellerbring, A.-K.; Andersson, L.-O. (Thrombosis and Haemostasis, 1979)
A newly developed sensitive method for determination of platelet factor 3 (PF 3) using a chromogenic substrate (S 2238) (Sandberg and Andersson, Thromb. Res., in press) was used for comparison of the PF 3 levels in platelet-rich plasma (PRP) in citrate with the levels in PRP in the anticoagulant EDTA/citrate/PCE 1/theophylline. It was shown that in citrate PRP, release of PF 3 was started after about 20 minutes from blood sampling. Release of β-thromboglobulin (β-tg) was found to occur simultaneously with the release of PF 3. No release of PF 3 or β-tg could be detected within 3 hours from blood sampling in PRP in the EDTA/citrate/PCE 1/theophylline anticoagulant.The PF 3 level in whole blood was measured by a method which was a modification of the method used for plasma samples. It was found that, using the same donor, the PF 3 level of plasma and blood in the EDTA/citrate/PCE 1/theophylline anticoagulant was essentially the same. The levels of PF 3 found in blood upon standing in citrate or in EDTA/citrate/PCE 1/theophy11ine anticoagulant were in accordance with the levels found in plasma. Experiments with whole blood without any anticoagulant showed that release of PF 3 begin to occur simultaneously with release of β-tg, about 5 minutes before clotting. Thus the data show that PF 3 and βtg are released in parallel.